2012
DOI: 10.3126/nepjoph.v4i2.6542
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome in open globe injuries

Abstract: Predictors of good visual outcome are good initial visual acuity, a corneal laceration wound of less than 5mm, a deep anterior chamber, and simple lacerations. Age, gender, place of injury, object causing injury, presence of hyphema or intraocular foreign body, and the use of safety precautions did not affect the visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
7
4
1
Order By: Relevance
“…In our study, patients with wounds that were smaller than 5 mm had a good prognosis for the visual outcome compared to patients with wounds that were larger than 5 mm ( p = 0.0078), which is in accordance with several previous reports [ 14 , 17 , 18 , 24 , 25 ]. A larger wound reflects more extensive ocular tissue damage and a higher likelihood of posterior involvement.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, patients with wounds that were smaller than 5 mm had a good prognosis for the visual outcome compared to patients with wounds that were larger than 5 mm ( p = 0.0078), which is in accordance with several previous reports [ 14 , 17 , 18 , 24 , 25 ]. A larger wound reflects more extensive ocular tissue damage and a higher likelihood of posterior involvement.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, the previous literature has also reported that the most frequently associated cause of trauma was occupational injury [ 11 , 13 , 18 , 19 ]. Other studies have confirmed that the majority of open-globe injuries occur in the home, ranging from 38 to 71% of the cases [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Penetrating injury by sharp tools is the major type of the ocular traumas in our study, which is consistent with previous studies showing that traumas are frequently caused by sharp objects following collisions [18,19,22,23]. Importantly, we found that penetrating injury is a major type of occupation related ocular traumas, as we observed a significant difference in several occupation groups regarding the types of ocular traumas.…”
Section: Discussionsupporting
confidence: 92%